Fatal Donor-Derived Carbapenem-Resistant Klebsiella pneumoniae Infection in a Combined Kidney-Pancreas Transplantation - Giovanni Varotti; Ferdinando Dodi; Anna Marchese; Alessia Terulla; Massimo Bertocchi; Iris Fontana (Case Reports in Transplantation)
Carbapenem-resistant Klebsiella pneumoniae (CR-KP) infections in solid organ transplant recipients are associated with high morbidity and mortality. We report a case of a fatal donor-derived CR-KP infection in a combined kidney-pancreas transplant. Given the short interval of time between donor hospitalization and organ procurement, information concerning the donor CR-KP positivity arrived only 72 hours after transplant. Based on this experience, we believe that knowledge of the donor’s CR-KP status should be mandatory before procurement and, if positive, pancreas donation should be contraindicated.